2015
DOI: 10.1186/s12913-016-1265-1
|View full text |Cite
|
Sign up to set email alerts
|

Downstream tests, treatments, and annual direct payments in older men cared for by primary care providers with high or low prostate-specific antigen screening rates using 100 percent Texas U.S. Medicare public insurance claims data: a retrospective cohort study

Abstract: BackgroundAll authorities recommend against prostate specific antigen (PSA) screening in men 75 years and older. However, some primary care physicians (PCPs) continue to have high rates of PSA, with large variation in testing. We assessed the tests, treatments, and payments for prostate cancer care in men aged 75 or older who have PCPs with high or low PSA testing rates.MethodsWe performed a retrospective cohort study using the 2010 Medicare beneficiaries aged 75 or older in Texas, United States who had no pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…This work is consistent with prior studies examining downstream implications of low-value PSA testing in older adults. 19 - 21 For example, Zanwar et al 21 compared downstream tests, treatments, and payments for prostate cancer care in older Texas Medicare beneficiaries cared for by primary care practitioners (PCPs) with high or low PSA screening rates. The authors similarly found that patients who were cared for by PCPs with high rates of PSA testing were more likely to visit a urologist or undergo prostate biopsy, ultrasound, or radiation compared with those who were cared for by PCPs with low rates of PSA testing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This work is consistent with prior studies examining downstream implications of low-value PSA testing in older adults. 19 - 21 For example, Zanwar et al 21 compared downstream tests, treatments, and payments for prostate cancer care in older Texas Medicare beneficiaries cared for by primary care practitioners (PCPs) with high or low PSA screening rates. The authors similarly found that patients who were cared for by PCPs with high rates of PSA testing were more likely to visit a urologist or undergo prostate biopsy, ultrasound, or radiation compared with those who were cared for by PCPs with low rates of PSA testing.…”
Section: Discussionmentioning
confidence: 99%
“…These services were defined by practicing clinicians on the research team, informed by their clinical knowledge and findings in relevant literature. 21 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PSA testing is ubiquitous and performed by a wide variety of clinicians outside of urology, with 34% of men aged ≥50 years and 40% of men aged ≥70 years receiving a PSA test in the prior year as of 2018 26 . The vast majority of tests occur in outpatient clinics, with over one‐half ordered by the patient's primary care physician 27 . Therefore, understanding the role of decision fatigue in PSA testing practices is of great importance to a broad range of clinicians aiming to increase value in their practices.…”
Section: Introductionmentioning
confidence: 99%
“…26 The vast majority of tests occur in outpatient clinics, with over one-half ordered by the patient's primary care physician. 27 Therefore, understanding the role of decision fatigue in PSA testing practices is of great importance to a broad range of clinicians aiming to increase value in their practices.…”
Section: Introductionmentioning
confidence: 99%